Validity and Reliability of Teachers’ Mathematics Competence Scale - Ghazali, Nor Hasnida Md; Bakar, Noor Insyirah Abu; Rusdin, Nor Azlin Mohd; Zaini, Syaza Hazwani; Hamzah, Mahizer (Current Progress in Arts and Social Studies Research Vol. 6, 2024)
Mathematical knowledge is very important to the mathematics teacher. The effectiveness of mathematic learning in the classroom heavily depends on the teacher's ability to facilitate learning. Exactly, teachers hoped to generate an effective and suitable curriculum for mathematical teaching. The aim of this study was to validate the mathematical knowledge scale based on the Earnest Framework in the Malaysian version. The respondents were 150 mathematics teachers from the north of Malaysia. A total of 26-item questionnaires examining mathematical knowledge were given to the participants. The validity of the scale was determined by using exploratory factor analysis with principal components analysis and varimax rotation. The number of factors through eigenvalues greater than one and frames the structure of the scale through factor loading re determined. The value of the eigenvalue and factor loading were considered in this research to frame and develop the structure of the scale. The reliability was tested with Cronbach's alpha. The appropriateness of the dataset to be used in factorial analysis was confirmed through KaiserMeyer-Olkin (KMO) and Barlett’s test of sphericity. The findings showed that six factors on the scale explaining 67.39% of the variances. 26 items with factor loading greater than 0.60 were determined for the scale. The structure of the scale was as follows; three items in the first factor, two items in the second factor, five items in the third factor, four items in the fourth factor, ten items in the fifth factor, and two items in the sixth factor. The reliability of the scale was 0.958. In conclusion, the scale is valid and reliable in measuring teachers’ mathematics knowledge. The scale can be used in research to examine the proficiency and mastery of the teacher in teaching mathematics.